2007
DOI: 10.1002/lsm.20459
|View full text |Cite
|
Sign up to set email alerts
|

Alternative denervation using laser irradiation in lumbar facet syndrome

Abstract: The dorsal surface of the facet capsule might be a more preferable target for facet denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, similar pain reduction or relief (81% at 1-year follow-up) was observed in CLBP patients treated by laser irradiation of the FJ capsule. 16 A more recent study experimented with 3-dimensional navigation for endoscopic rhizotomy, yet it remains unclear whether this technique yields better outcomes. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, similar pain reduction or relief (81% at 1-year follow-up) was observed in CLBP patients treated by laser irradiation of the FJ capsule. 16 A more recent study experimented with 3-dimensional navigation for endoscopic rhizotomy, yet it remains unclear whether this technique yields better outcomes. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Schaerer 13 reported good to excellent results in 50% of patients with cervical facet disease and 35% of patients with lumber disease after a mean follow-up of 13.7 months. Iwatsuki et al 5 reported significant pain relief in 71% of 21 patients at one year follow-up with laser denervation of the dorsal facet capsule. Li et al 8 treated 5 patients with RFA of the dorsal rami.…”
Section: Discussionmentioning
confidence: 99%
“…There is comparable efficiency of endoscopic facet debridement to radiofrequency ablation of the dorsal nerve [50]. Laser denervation of the dorsal capsule of the facet joint appears to be a more preferable target for facet joint denervation [51].…”
Section: Alternate Techniquesmentioning
confidence: 98%